2006
DOI: 10.1002/anie.200504275
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Substrate Binding by the Lanthanide Centers in [Li3(thf)n(binolate)3Ln]: Solution and Solid‐State Characterization of Seven‐ and Eight‐Coordinate [Li3(sol)n(binolate)3Ln(S)m] Adducts

Abstract: Ln] (binol = 1,1'-bi-2-naphthol; M = Li, Na, K; thf = tetrahydrofuran) catalysts (Figure 1) developed by Shibasaki and co-workers have proven to be among the most versatile and successful asymmetric Lewis acid catalysts introduced to date. [1][2][3] Central to mechanistic proposals involving [M 3 A C H T U N G T R E N N U N G (thf) n -A C H T U N G T R E N N U N G (binolate) 3 Ln] heterobimetallic compounds is Lewis acid activation of the substrate by the lanthanide. [2][3][4] Prior efforts to detect lanthani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(9 citation statements)
references
References 20 publications
1
8
0
Order By: Relevance
“…Salvadori reported that YbNaB does not bind water, and related observations were made by Shibasaki and Aspinall . We found that the DMF formyl C–H shifted over 4 ppm in the presence of YbLiB in THF, but no LIS was observed in the presence of RENaB (RE = Yb and Eu) or YbKB under identical conditions . Further insight came from the SC-XRD studies of anhydrous RENaB (RE = La III and Eu III ).…”
Section: Understanding and Expansion Of The Catalysis Of Shibasaki’s ...supporting
confidence: 68%
See 1 more Smart Citation
“…Salvadori reported that YbNaB does not bind water, and related observations were made by Shibasaki and Aspinall . We found that the DMF formyl C–H shifted over 4 ppm in the presence of YbLiB in THF, but no LIS was observed in the presence of RENaB (RE = Yb and Eu) or YbKB under identical conditions . Further insight came from the SC-XRD studies of anhydrous RENaB (RE = La III and Eu III ).…”
Section: Understanding and Expansion Of The Catalysis Of Shibasaki’s ...supporting
confidence: 68%
“…For example, substrate binding at a paramagnetic RE III center (e.g., Pr III , Eu III ) would induce significant changes in substrate chemical shifts (lanthanide-induced shifts, LISs); however, minimal shifts were observed for the formyl C–H of pivaldehyde in the presence of PrNaB and EuNaB . Therefore, we undertook a series of binding studies to understand the activation mode of REMB. , …”
Section: Understanding and Expansion Of The Catalysis Of Shibasaki’s ...mentioning
confidence: 99%
“…Shibasaki's M 3 (THF) n (BINOLate) 3 Ln complexes (Figure ) are among the most effective asymmetric Lewis acid catalysts known, exhibiting high enantioselectivities over a broad range of reactions. Understanding how these heterobimetallic catalysts work, however, has proven challenging. In particular, seemingly subtle alterations in the catalyst composition result in dramatic changes in selectivity. For example, in the nitro aldol reaction with M 3 (THF) n (BINOLate) 3 Ln, 94% ee was obtained when M = Li and 2% ee was obtained when M = Na.…”
mentioning
confidence: 99%
“…We recently demonstrated that DMF reversibly binds to paramagnetic lanthanides in Li 3 (THF) n (BINOLate) 3 Ln (Ln = Eu, Pr), exhibiting a >2 ppm lanthanide induced shift (LIS) in the formyl C−H resonance in the 1 H NMR spectrum . Salvadori, on the other hand, reported 7 that Na 3 (THF) 6 (BINOLate) 3 Yb does not bind water in solution or in the solid state, which was attributed to the small ionic radius of Yb (La = 1.17, Eu = 1.09, Yb = 1.01).…”
mentioning
confidence: 99%
“…The highly ordered structure of RE-M [1] 3 -tris­(BINOLate) has attracted sustained interest in the chemical community, and in-depth studies were conducted to dissect the coordination dynamics of this class of complexes . Walsh et al revealed hepta- and octa-coordinated RE in the crystal structures of these complexes with ligated guest molecules, while NMR experiments suggested a dynamic exchange of Li + and BINOL units in solution. The exchange kinetics are faster than the reactions, and the involvement of a putative bis­(BINOLate) species (or oligomeric multimetallic species) was proposed. Although the mode of action of RE-M [1] 3 -tris­(BINOLate) is mostly Lewis acid/Brønsted base cooperative catalysis, Lewis acid/Lewis acid cooperative catalysis would be operative in aza-Michael reactions, Corey–Chaykovsky cyclopropanation, and epoxidation, where both RE and M [1] function as Lewis acids to activate nucleophiles and electrophiles.…”
Section: Multimetallic Catalystsmentioning
confidence: 99%